2020
DOI: 10.3390/ijerph17228397
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the Hong Kong Youth Quitline Service and Quitting Behaviors of Its Users

Abstract: Tobacco use is a possible risk factor for contracting and spreading COVID-19. We aimed to describe the impact of the COVID-19 pandemic on the Youth Quitline service and quitting behaviors of its users in Hong Kong. We conducted a telephone survey involving 201 participants of the Youth Quitline service, and retrospectively analyzed the operation and use of Quitline since the COVID-19 outbreak in Hong Kong. The number of incoming calls to the Youth Quitline and the participants′ quit rate has increased since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 17 publications
3
35
1
Order By: Relevance
“…Increased tobacco use during the pandemic has been also reported in recent studies [39,41,46]. Besides, many current smokers in our study have reported their intention to quit smoking during the pandemic, which was also one of the findings of various studies during the pandemic crisis [37,41]. Various COVID-19 related reasons were cited by quit planners during the pandemic (among current smokers) and successful quitters during the pandemic (among ex-smokers).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Increased tobacco use during the pandemic has been also reported in recent studies [39,41,46]. Besides, many current smokers in our study have reported their intention to quit smoking during the pandemic, which was also one of the findings of various studies during the pandemic crisis [37,41]. Various COVID-19 related reasons were cited by quit planners during the pandemic (among current smokers) and successful quitters during the pandemic (among ex-smokers).…”
Section: Discussionsupporting
confidence: 84%
“…Besides, the pandemic-induced social, economic, and psychological impacts may affect smoking-related behaviors and attitudes among current smokers [32][33][34][35]. On the other hand, this pandemic might encourage tobacco users to quit smoking considering the reported association between smoking and adverse outcomes of COVID-19 compared to non-smokers [35][36][37]. Considering the importance of understanding people's beliefs about smoking and its implications on developing targeted interventions and smoking cessation programs, and in the line with the previously described pandemic impacts, the linkage between smoking and COVID-19, the high smoking rates in Jordan, and the paucity of studies that assessed this topic during the pandemic in the EMR, our current study aims were (i) to assess and explore the attitudes and beliefs that surround smoking/vaping and COVID-19 (ii) to assess the impacts of the pandemic on smoking behaviors and quit plans/attempts, in a community-based sample from Jordan.…”
Section: Study Rationale and Aimsmentioning
confidence: 99%
“…They reported improved attendance and engagement at telehealth visits compared to prior in-person visits. Another study conducted among current smokers <25 years old who participated in the Youth Quitline services in Hong Kong found that over 4-in-10 agreed the pandemic was a motivator to quit tobacco use, over 7-in-10 changed their tobacco use habits due to public health measures (e.g., wearing a mask), and nearly 6-in-10 reduced their daily cigarette consumption ( 53 ). Therefore, telemedicine has the potential to decrease patient-level barriers to in-person tobacco cessation treatment among all ages worldwide, such as lack of transportation, childcare, and travel costs.…”
Section: Tobacco Use and Covid-19mentioning
confidence: 99%
“…Besides, the pandemic-induced social, economic, and psychological impacts may affect smoking-related behaviors and attitudes among current smokers (32)(33)(34)(35). On the other hand, this pandemic might encourage tobacco users to quit smoking considering the reported association between smoking and adverse outcomes of COVID-19 compared to non-smokers (35)(36)(37). Considering the importance of understanding people's beliefs about smoking and its implications on developing targeted interventions and smoking cessation programs, and in the line with the previously described pandemic impacts, the linkage between smoking and COVID-19, the high smoking rates in Jordan, and the paucity of studies that assessed this topic during the pandemic in the EMR, our current study aims were (i) to assess and explore the attitudes and beliefs that surround smoking/vaping and COVID-19 (ii) to assess the impacts of the pandemic on smoking behaviors and quit plans/attempts, in a community-based sample from Jordan.…”
Section: Study Rationale and Aimsmentioning
confidence: 99%
“…A structured questionnaire was developed by the authors after reviewing relevant and related literature (19,35,37,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). The questionnaire comprised 39 single-answer items that were distributed over three sections as the following:…”
Section: Assessment Tool and Measuresmentioning
confidence: 99%